Failure Analysis on 42CrMo Steel Bolt Fracture - Guo Hongfei; Jianwei Yan; Ru Zhang; Zhihui He; Zengqi Zhao; Ting Qu; Ming Wan; Jingshun Liu; Congdong Li (Advances in Materials Science and Engineering)
Fracture behaviors of 42CrMo ultrahigh strength steel-based bolt have been experimentally studied including macroscopic and microscopic fracture observation, metallographic test, mechanical property testing, and energy spectrum analysis. The results show that a large amount of structure defects, such as sulfide inclusions, band, and carbon depletion, appear in the fracture origin region and matrix of the bolt. Such defects reduce fatigue strength of materials and easily yields fatigue fracture origin. In addition, sulfide inclusions provide easy access to crack growth, gradually reducing the effective cross section of the bolt accompanying with increasing stress and finally causes fracture when stress exceeds the material fracture strength. The fracture mechanism is also explored based on fracture failure criterion and fatigue crack growth curve.